2016
DOI: 10.1111/iju.13145
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from the tumor microenvironment as reciprocal regulators that enhance prostate cancer progression

Abstract: Distant organ metastasis of prostate cancer is a puzzle, and various theories have successively arisen to explain the mechanism of lethal cancer progression. While perhaps agreeable to many cancer biologists, the very statement of "seed and soil" proposed by Stephan Paget in 1881 is arguably still the major statement for organspecific cancer metastasis. Since recent studies showed important correlations of regulation of cancer cells and the microenvironment, exosomes from cancer and stromal cells seem to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 139 publications
(131 reference statements)
1
40
0
Order By: Relevance
“…The study of organ‐specific metastasis to the brain has been gradually gaining recognition nowadays. Nevertheless, a lot of brain‐derived factors are developed in recent studies, including secreted proteins and microRNA‐containing exosomes which alter the brain microenvironment to facilitate the survival and growth of BM 12, 13. Extracellular vesicles (EVs) including exosomes, mediate cell to cell communication with the delivery of their contents and then adjust multiple factors of malignancy in cancer cells 14, 15.…”
Section: The Hypothesis About the Origin Of Bmmentioning
confidence: 99%
“…The study of organ‐specific metastasis to the brain has been gradually gaining recognition nowadays. Nevertheless, a lot of brain‐derived factors are developed in recent studies, including secreted proteins and microRNA‐containing exosomes which alter the brain microenvironment to facilitate the survival and growth of BM 12, 13. Extracellular vesicles (EVs) including exosomes, mediate cell to cell communication with the delivery of their contents and then adjust multiple factors of malignancy in cancer cells 14, 15.…”
Section: The Hypothesis About the Origin Of Bmmentioning
confidence: 99%
“…The canonical proteins in exosomes could be identi ed, such as heat shock proteins, cytoskeletal proteins, endosomal molecules, multivesicular tetraspanins, antigen presentation molecules, adhesion proteins, immunoglobulin family members, and so on [21]. Moreover, exosomal proteins speci c for DU145 cells were detected, exempli ed by integrin family members, CD276, ANXA2, CLSTN1, FASN, and FLNC [7]. These results demonstrated that exosomes from PC DU145 cells not only have similar features as exosomes from other cell types but also have speci c characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that tumor-derived exosomes can be uptaken by speci c organs or cells, to create favorable TME for cancer metastasis. For example, miR-21, miR-141, and miR-375 enriched exosomes derived from PC play important roles in assisting tumor cells to acclimatize to the low-androgen environment of distant metastatic organs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies point out that exosomes released from the tumor microenvironment can regulate (also by tethering TGFβ) a proliferation, a reduction of apoptosis, a promotion of angiogenesis and, finally, an evasion of immune surveillance ( Figure 2). Moreover, exosomes can provide candidate biomarkers for prostate cancer, contribute to tumor progression and, after a loss of environment homeostasis, promote tumor metastasis [18]. Role of prostate cell-derived exosomes in cancer progression.…”
Section: Introductionmentioning
confidence: 99%